2011
DOI: 10.1007/s00405-011-1663-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of lymph node metastasis in early-stage parotid gland cancer

Abstract: Lymph node metastasis is one of the most important factors in therapy and prognosis for patients with parotid gland cancer. Nevertheless, the extent of the primary tumor resection and the necessity of a neck dissection still is a common issue. Since little is known about lymph node metastasis in early-stage parotid gland cancer, the purpose of the present study was to evaluate the occurrence of lymph node metastases in T1 and T2 carcinomas and its impact on local control and survival. We retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 18 publications
10
72
1
1
Order By: Relevance
“…I, III and V levels were involved in approximately 20% (±3%), while level IV was involved in only one series (<10%). Involvement of level V, especially Va, is not that obvious (3/6 series) and most probably it is associated with location and local stage of the tumour [3, 1012, 15]. In the presented series and two other ones, there were no metastases in level I either [3, 11].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…I, III and V levels were involved in approximately 20% (±3%), while level IV was involved in only one series (<10%). Involvement of level V, especially Va, is not that obvious (3/6 series) and most probably it is associated with location and local stage of the tumour [3, 1012, 15]. In the presented series and two other ones, there were no metastases in level I either [3, 11].…”
Section: Discussionmentioning
confidence: 82%
“…Lim et al showed that patients with cN0 neck and I/PLN metastases have statistically significant higher chance of locoregional recurrence and poorer prognosis [17]. In the published results from series of patients with cN0 salivary gland carcinomas, I/PLN metastases were coexistent with occult neck metastases (30–80%) [3, 5, 10, 12]. Some authors recommend total parotidectomy even in patients with early stage parotid gland carcinomas, since it is the only way to remove and identify all I/PLN metastases [3, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37, 38] Elective neck dissection (END) should be indicated when the risk of subclinical disease in a clinically negative neck exceeds 15%. [36] Hence, it would be of great value to formulate a criteria to select patients for whom a neck dissection should be incorporated into the surgical management of the primary tumor.…”
Section: Elective Neck Dissectionmentioning
confidence: 99%
“…Firstly, lymph nodes existed in both lobes of the parotid gland, undiagnosed metastatic IPNs might be caused by non-total parotidectomy, and then recurrent disease might be expected owing to the residual disease. Therefore, total parotidectomy was suggested for all parotid cancer patients by previous authors [15]. The high 10-year RFS rate in current study came into our attention, it was better than previous researches [8, 11], the favorable outcome might be partially explained by our routine total parotidectomy.…”
Section: Discussionmentioning
confidence: 50%